2010
DOI: 10.1111/j.1442-2050.2010.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of multimodality therapy for stage IVB esophageal cancer with distant organ metastasis (M1-Org)

Abstract: Esophageal cancer patients with distant organ metastasis have usually been treated only to palliate symptoms without multimodality therapy. The current study evaluates the role of multimodality therapy in esophageal squamous cell cancer patients with distant organ metastasis. Between February 1988 and January 2007, 80 esophageal squamous cell cancer patients with distant organ metastases were treated at our institution. Multimodality therapy was performed in 58 patients: 43 patients received chemoradiotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 24 publications
0
62
0
Order By: Relevance
“…This indicated that, on the basis of chemotherapy, the treatment of primary esophageal lesions may improve the survival of esophageal cancer patients with distant organ metastasis. 14 With regards to multimodality treatment, the difference in survival between surgery combined with chemotherapy and radiotherapy combined with chemotherapy was not statistically significant ( p ¼ 0.147), suggesting that either surgery or radiotherapy as a local treatment may be feasible for newly diagnosed distant organ metastasis from esophageal cancer. 15 However, due to the limited number of cases receiving multimodality treatment, our results require confirmation through the accumulation of more cases and further prospective clinical trials.…”
Section: Discussionmentioning
confidence: 83%
“…This indicated that, on the basis of chemotherapy, the treatment of primary esophageal lesions may improve the survival of esophageal cancer patients with distant organ metastasis. 14 With regards to multimodality treatment, the difference in survival between surgery combined with chemotherapy and radiotherapy combined with chemotherapy was not statistically significant ( p ¼ 0.147), suggesting that either surgery or radiotherapy as a local treatment may be feasible for newly diagnosed distant organ metastasis from esophageal cancer. 15 However, due to the limited number of cases receiving multimodality treatment, our results require confirmation through the accumulation of more cases and further prospective clinical trials.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies questioned the prognostic value of palliative resection of primary tumor. Tanaka et al investigated 80 metastatic esophageal squamous cell carcinoma patients, and found no difference in survival for palliative resection group and patients without resection . Saddoughi et al estimated 52 stage IV EC patients with palliative surgery in their institution.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of esophageal cancer patients is dismal, especially those with distant organ metastases (2). Poor outcomes in patients with esophageal cancer are related to the propensity for metastases, even when tumors are superficial (2,3) and lack of effective treatment modality for those with distant metastasis (4). However, there are few studies describing the patterns of distant metastasis in esophageal cancer systematically.…”
Section: Introductionmentioning
confidence: 99%